A methodology for ontological knowledge capture from databases - García-Sánchez, F.; Fernández-Breis, J.T.; Martínez-Bejar, R. (Інститут програмних систем НАН України, 2008)
The successful emergence of the Information and Communication Technologies (ICT) has contributed to the efficiency improvement in a number of economic sectors. However, some strategic economic sectors, such as construction, have not been targeted enough yet. Construction-related ICT solutions lack mechanisms to permit the effective integration of the whole supply chain. Semantic Web can tackle these issues. This paper presents a methodology for acquiring knowledge from construction-related databases. A domain ontology has been developed that contains the relevant concepts regarding supply management in the construction domain. The methodology basically consists of mapping the database content onto the ontology and a further this one’s population by applying a set of mapping rules.